2003
DOI: 10.1023/b:qinp.0000004123.82268.f4
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model for Quantum Measurement

Abstract: Is the dynamical evolution of physical systems objectively a manifestation of information processing by the universe? We find that an affirmative answer has important consequences for the measurement problem. In particular, we calculate the amount of quantum information processing involved in the evolution of physical systems, assuming a finite degree of fine-graining of Hilbert space. This assumption is shown to imply that there is a finite capacity to sustain the immense entanglement that measurement entails… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…A fundamental assumption of the CMQM is that Hilbert space is discrete [36,37]. The idea of a discrete Hilbert space has been independently arrived at in Ref.…”
Section: Computational Model For Quantum Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…A fundamental assumption of the CMQM is that Hilbert space is discrete [36,37]. The idea of a discrete Hilbert space has been independently arrived at in Ref.…”
Section: Computational Model For Quantum Measurementmentioning
confidence: 99%
“…Wavefunction collapse is thus understood as an algorithmic (rather than dynamic) process or transition. It can be shown that repeated cycles of collapse and episodes of µ-unitary evolution lead to macro-classicality compatible with the decoherence of an open system [36,37]. An implication for quantum computation is that asymptotically, the power of QCs is not BQP but BPP, since the degree of superposition (the degree of quantum parallelism) is upper-bounded by 2 µ .…”
Section: Computational Model For Quantum Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, information loss is not worrisome in collapse models of quantum measurement, where state vector reduction already represents a source of fundamental, irreversible randomness (cf [14],. and references therein).…”
mentioning
confidence: 99%